Comecei a sonhar com homens: a "saída do armário" vivenciada por homossexuais masculinos em suas interações familiares - Oliveira, Givaldo Moises de (2019)
This dissertation presents a study on the "coming out of the closet", a category that identifies the path of making homosexuality public. The research aimed to describe the path followed by homosexual men who decided to make public a sexual orientation marked by stigma, prejudice and violence. The objective was to identify how this decision was made and its implications. The research was based on interviews with ten openly homosexuals who live in Foz do Iguaçu. The adopted methodology was a qualitative approach, with the semi-structured interview as the main instrument for data collection. The analysis of the collected information was guided by the Goffmanian dramaturgical perspective, which analyzes social relations from the theatrical metaphor. To become “out of the closet” can be understood as an act that allows the homosexual actor to face the stigmata and to search for equality among the other individuals in all social dimensions.